Prognostic Significance of Circulating Immune-Inflammatory Biomarkers IL-6 and Systemic Immune-Inflammation Index in Hepatocellular Carcinoma Treated With Immune Checkpoint Inhibitors: A Meta-Analysis: Circulating Immune-Inflammatory Biomarkers in HCC - Hu, Enze; Qiu, Yuanfu (Journal of Medical Biochemistry, 2026)
Background: Hepatocellular carcinoma (HCC) is characterized by a chronic inflammatory and immunologically dysregulated microenvironment. Circulating immune-inflammatory biomarkers reflect systemic biochemical and immune alterations and may provide laboratory-accessible indicators for prognosis assessment. However, the prognostic value of interleukin-6 (IL-6) and the systemic immune-inflammation index (SII) in HCC patients receiving immune checkpoint inhibitors (ICIs) remains incompletely defined. Methods: A comprehensive literature search was conducted across PubMed, Embase, Web of Science, the Cochrane Library, CNKI, and Wanfang Data to identify cohort studies evaluating circulating IL-6 and/or SII in HCC patients treated with ICIs. Hazard ratios (HRs) with 95% confidence intervals (CIs) for progression-free survival (PFS) and overall survival (OS) were pooled using fixed- or random-effects models. Subgroup and sensitivity analyses were performed to explore sources of heterogeneity. Results: Twelve studies involving 1,508 patients were included. Elevated circulating IL-6 levels were significantly associated with poorer PFS (HR = 1.91, 95% CI 1.40–2.60) and OS (HR = 2.13, 95% CI 1.52–2.97), with robust results across sensitivity analyses. In contrast, the prognostic value of SII was context-dependent. Higher SII was significantly associated with shorter PFS in non-100% hepatitis B virus–related HCC populations and with poorer OS in patients receiving combined local treatment, while no significant associations were observed in other subgroups. Conclusions: Circulating IL-6 serves as a stable immune-biochemical prognostic biomarker in HCC patients treated with ICIs, whereas the prognostic relevance of SII is modulated by disease etiology and treatment modality. These findings provide laboratory-relevant biochemical evidence supporting the integration of circulating immune-inflammatory markers into prognostic evaluation frameworks for HCC.